Intimate entanglements in the ethnography of performance : race, gender, vulnerability - Lawrence, Sidra; Kisliuk, Michelle Robin; Kapchan, Deborah A. (Deborah Anne) (Eastman/Rochester studies in ethnomusicology, 2023)
"Focused on research within Africa and the African diaspora, contributors to this volume think through the painful iterations of trauma, systemic racism, and the vestiges of colonial oppression as well as the processes of healing and emancipation that emerge from wounded states. Their chapters explore an acoustemology of intimacy, woman-centered eroticism generated through musical performance, desire and longing in ethnographic knowledge production, and listening as intimacy. On the other end of the spectrum, authors engage with and question the fetishization of race in jazz; examine conceptions of vulgarity and profanity in movement and dance-ethnography; and address pain, trauma, and violation, whether physical, spiritual, intellectual, or political. Authors in this volume strive toward empathetic, ethical, and creative ethnographic engagements that summon vulnerability and healing. They propose pathways to aesthetic, discursive transformation by reorienting conceptions of knowledge as emergent, performative, and sonically enabled. The resulting book explores sensory knowledge that is frequently left unacknowledged in ethnographic work, advancing conversations about performed sonic and somatic modalities through which we navigate our entanglements as engaged scholars"--